A new design of the continual reassessment method. Issue 7 (12th August 2021) - Zhang, Weijia; Wang, Xikui; Yang, Po
Abstract: We propose a new design of the continual reassessment method and systematically evaluate its performance on certain operating measures to satisfy the requirements of collective and individual ethics. Simulation results are derived to compare the new design with currently available designs on criteria BEARS: Benchmark, Efficiency, Accuracy, Reliability, Safety. Overall, the new design performs well and safely avoids toxic doses (hence safeguarding individual ethics) while reliably identifying the maximum tolerated dose (hence protecting collective ethics).